CO2 Absorption Using Biogas Slurry: CO2 Absorption Enhancement Induced by Biomass Ash. (July 2017) - Yan, Shuiping; He, Qingyao; Wang, Wenchao; Li, Shefeng
Abstract: Biogas slurry can be adopted as a renewable CO2 absorbent to combine CO2 absorption with CO2 biological fixation. However its CO2 absorption performance should be enhanced. In the study, biomass ash was adopted as the additive to increase free ammonia concentration in the biogas slurry. And the effect of biomass ash dosage on CO2 absorption performance of biogas slurry was investigated in the typical bubbling absorption apparatus. Additionally, phytotoxicity of CO2 -rich biogas slurry before or after adding biomass ash was experimented as well in terms of the germination index of Chinese cabbage seeds. Results showed that CO2 absorption performance of biogas slurry can be enhanced by adding biomass ash due to the leaching of some alkaline substances from biomass ash, and net CO2 absorption capacity of biogas slurry generally increases with the biomass ash dosage. Cotton stalk ash has the best performance because net CO2 absorption capacity can increase to by about 600% compared to that of raw biogas slurry when the dosage is about 200 g/L. After adding biomass ash, CO2 -rich biogas slurry still has low phytotoxicity to the germination of cabbage seeds. When high CO2 absorption capacity, low phytotoxicity and low biomass ash dosage are all considered, 100 g/L may be the optimal dosage for cotton stalk ash. In addition, the dosage of 50 g/L should be considered for rich straw ash and corn stalk ash. However, 200 g/L should be added into biogas slurry for groundnut shell ash.